The effect of Russia's economic crisis and import ban on its agricultural and food sector. Issue 2 (July 2019) - Liefert, William M; Liefert, Olga; Seeley, Ralph; Lee, Tani
This article examines how Russia's economic crisis and ban on agricultural imports from the United States and other Western countries that began in 2014 have impacted its agricultural and food sector. The import ban was a Russian response to geopolitical tension with the West stemming from the country's conflict with Ukraine, while the main cause of the economic crisis was a plunge in world oil prices. Given that the bulk of Russia's export earnings come from oil and other energy products, the oil price decline triggered a major depreciation of the ruble against the US dollar and other major currencies. Ruble depreciation and the import ban have affected Russian consumers by reducing Russia's imports of agricultural and food products, substantially raising food prices, and lowering consumption. However, the country's basic food availability has not been threatened. By increasing domestic prices, the depreciation and import ban have stimulated agricultural production. The added output has reduced meat imports and raised grain exports. Russian meat imports in 2014–2016 (average annual) were about 40% lower compared to 2011–2013, while grain exports in 2014–2016 were 50% higher than in 2011–2013 (though production-enhancing favorable weather was also a cause).